2016
DOI: 10.1371/journal.pone.0157234
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Culture-Free Detection of Staphylococcus aureus Bacteremia

Abstract: S. aureus bacteremia (SAB) is a common condition with high rates of morbidity and mortality. Current methods used to diagnose SAB take at least a day, and often longer. Patients with suspected bacteremia must therefore be empirically treated, often unnecessarily, while assay results are pending. In this proof-of-concept study, we describe an inexpensive assay that detects SAB via the detection of micrococcal nuclease (an enzyme secreted by S. aureus) in patient plasma samples in less than three hours. In total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…10 We recently described rapid assays based on this same concept for focal S. aureus infections 12 and S. aureus bacteremia. 13 To the best of our knowledge, there has been no other description of a rapid assay that detects a disease by detecting the activity of a disease-associated nuclease. Our identification of endonuclease I as a novel biomarker for E. coli and our demonstration that its activity can be used to rapidly detect an E. coli infection therefore demonstrates the broader value and potential of nuclease-based assays for diagnosing infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 We recently described rapid assays based on this same concept for focal S. aureus infections 12 and S. aureus bacteremia. 13 To the best of our knowledge, there has been no other description of a rapid assay that detects a disease by detecting the activity of a disease-associated nuclease. Our identification of endonuclease I as a novel biomarker for E. coli and our demonstration that its activity can be used to rapidly detect an E. coli infection therefore demonstrates the broader value and potential of nuclease-based assays for diagnosing infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Because nucleases are very diverse 14 and are essential for life, 14 nuclease probes that selectively detect alternative bacterial pathogens may also be developed. Moreover, antibodies that selectively inhibit 9 or immuno-precipitate 13 target nucleases can be incorporated into nuclease assays to yield detection and discrimination of multiple uropathogens. We envision a rapid multiplexed nuclease assay that incorporates such approaches for the differential diagnosis of UTI with coverage of several bacterial species as a rapid diagnostic alternative to the commonly used dipstick (which lacks sensitivity) and culture (which is time consuming).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated the sensitivity of our nuclease-activated probe technology by detecting attomolar (10 −18 molar) levels of a bacterial nuclease in the human plasma. (239) In the present study, we sought to exploit the potential of the nucleaseactivated probe technology to diagnose cancer. The challenge here was to reliably distinguish between mammalian nucleases expressed in cancer cells versus those expressed in leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The assay steps include: (1) capture of cancer cells, which is performed within 10 min with commercially available microfiltration units from SCREENCELL, (2) lysis of cancer cells using an optimized nuclease digestion buffer that contains the chemically optimized nuclease probes, and (3) signal detection using standard fluorometry technology.We previously demonstrated the utility of quenched fluorescent nucleic acid probes for the detection of bacterial nucleases (237,238). In this initial study, we demonstrated a sensitivity in the low attomolar (10 −18 molar) range for the detection of a bacterial nuclease in human plasma (239). In this study, we performed key technical modifications for adapting this technology for the detection of endogenous nucleases in cancer patients.…”
mentioning
confidence: 97%